Training Manual for Effective Service Delivery and Security Measures in the Nigerian Police Force - Oshodi, John Egbeazien (2011)
There is increasing concern about insecurity in the nation and the modern Nigerian police force, now in its 81st year, still needs improvement in the area of psychological readiness in order to effectively protect life and property of the people. In this article it is argued that a highly functional police system usually begins with a psychologically competent police man or woman; as such, a psychological-based manual is being proposed.In the 21st century the road to the internal security of the nation will only open widely when the police organization enhances its functional performance and fulfills its proper role in society using officers and resources that are psychologically and emotionally adequate. This paper provides an overview of the essential procedural aspects of the pre-employment psychological screening process for potential law enforcement officer candidates and for post-psychological updates and followups for serving officers. This paper presents the basic steps of the psychological screening process and argues for it to become standard, mandated requirements of the nation. In this article the characteristics and the attributes looked for in law enforcement candidates through the psychological screening process are explained. Keywords: police, testing, competent, manual, training, psychological, psychologist